Integrating migration, human development and remittances: an analysis of SAARC countries. (23rd April 2019) - Kausar, Farzana; Sarwar, Saima; Rafiq, Muhammad Yasir; Ali, Rizwan; Rehman, Ramiz Ur
This study explores the influence of migration on human development and remittances which eventually leads to international migration. In order to achieve this objective data were collected from 2000 to 2014 for remittances, human development, migration, political openness, population, political stability, corruption, trade and foreign direct investment for SAARC countries. Results of the study revealed that migration, trade, population, political openness, and corruption were significant and have an impact on human development and remittances. The inclusive outcome of this study by testing penal techniques: majority panel statistics reject the null hypothesis. We may conclude that migration is co-integrated with human development and remittances. The rationale of this study is supportive of policymakers, investors, traders, and economic researchers.